2017
DOI: 10.4049/jimmunol.1700845
|View full text |Cite|
|
Sign up to set email alerts
|

Palmitate Conditions Macrophages for Enhanced Responses toward Inflammatory Stimuli via JNK Activation

Abstract: Obesity is associated with low-grade inflammation and elevated levels of circulating saturated fatty acids, which trigger inflammatory responses by engaging pattern recognition receptors in macrophages. Because tissue homeostasis is maintained through an adequate balance of pro- and anti-inflammatory macrophages, we assessed the transcriptional and functional profile of M-CSF-dependent monocyte-derived human macrophages exposed to concentrations of saturated fatty acids found in obese individuals. We report th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 61 publications
1
46
0
Order By: Relevance
“…Herafill® granules consist of calcium sulfate, calcium carbonate and glycerine tripalmitate as bonding additive (Heraeus Medical GmbH, ). Palmitate is a saturated nonesterified fatty acid (NEFA) which is known to induce a proinflammatory and immunogenic response in human monocytes and cause synthesis and secretion of IL‐6 and TNF‐α (Bunn et al, ; Riera‐Borrull et al, ). Furthermore, palmitate increases the secretion of proinflammatory adipokines monocyte chemoattractant protein‐1 (MCP‐1) and vascular endothelial growth factor (VEGF) (Kitahara et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herafill® granules consist of calcium sulfate, calcium carbonate and glycerine tripalmitate as bonding additive (Heraeus Medical GmbH, ). Palmitate is a saturated nonesterified fatty acid (NEFA) which is known to induce a proinflammatory and immunogenic response in human monocytes and cause synthesis and secretion of IL‐6 and TNF‐α (Bunn et al, ; Riera‐Borrull et al, ). Furthermore, palmitate increases the secretion of proinflammatory adipokines monocyte chemoattractant protein‐1 (MCP‐1) and vascular endothelial growth factor (VEGF) (Kitahara et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it could be evidenced that increased palmitate‐concentration has impact on the polarization of macrophages and their reactivity on inflammatory stimuli via activation of JNK‐kinases (Riera‐Borrull et al, ). Also, evidence is found that high doses of palmitate significantly influence the differentiation of bone marrow‐derived macrophages and promote the anti‐inflammatory M2‐subtype.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro incubation of mouse and human monocyte/macrophage cell lines in media containing high concentrations of glucose or free fatty acids (FFAs) induces increased IL-1β production. This suggests that metabolic stress in obesity and/or T2DM can stimulate islet macrophages to produce more IL-1β 10,65,66 . Indeed, while both β-cells and macrophages can produce IL-1β, macrophages are seemingly the major source of islet IL-1β production in obesity 10,64 .…”
Section: Soluble Factorsmentioning
confidence: 99%
“…We investigated whether macIDR was capable of discerning GM-CSF-differentiated MDMs (GM-MDMs) exposed to various stimuli. In total, we obtained 31 datasets from three microarray studies ( 5, 16, 39 ) where GM-MDMs were activated with LPS (GM-LPS early , GM-LPS late ), IFNγ (GM-IFNγ), and IL4 (GM-IL4), or remained unstimulated (GM0). These studies were selected based on their similarity in activation duration with the M-CSF differentiated macrophages used in the training set.…”
Section: Resultsmentioning
confidence: 99%
“…To understand the limitations of macIDR, we investigated its performance on non-MDM cells. Datasets were obtained of monocyte-derived dendritic cells (MoDC) ( 5, 39 ), various T lymphocyte subtypes (T), B lymphocytes (B), neutrophils (NP), and natural killer cells (NK) ( 16, 40 ), as well as fibroblast-like synoviocytes (FLS) ( 27 ).…”
Section: Resultsmentioning
confidence: 99%